Priority For Strengthening Manpower Institutional Capacity In North Maluku Province - Abdullah Wajir Jabid; Bakri Soamole; Rahman Dano Mustafa (Jurnal Economia, 2022)
AbstractThe main problem of employment includes the amount of open unemployment, the low quality of the workforce (low competency), low work productivity, and low welfare of workers, so workforce planning is needed that can be used as a reference by all stakeholders in picking up investments in North Maluku Province. The purpose of this study is to look into the strategy for establishing and expanding workforce competency in various investment priorities in North Maluku Province. The goal is to enhance worker competency in the short and medium term; consequently, the quality of Job Training Centers must be prioritized (JTC). Furthermore, downstreaming agriculture and fisheries is a critical investment priority for preparing its workforce for competence, because it is commensurate with the characteristics and potential of local resources, as well as geographical considerations and sustainability guarantees.Keywords: Employment, competitiveness, investment, inclusive growth, AHPPrioritas Kompetensi Tenaga Kerja Untuk Daya Saing Investasi Di Provinsi Maluku Utara Abstrak Masalah utama ketenagakerjaan diantaranya adalah besarnya pengangguran terbuka, rendahnya kualitas angkatan kerja (kompetensi rendah), rendahnya produktivitas kerja, dan rendahnya kesejahteraan pekerja, sehingga diperlukan perencanaan tenaga kerja yang dapat dijadikan acuan oleh seluruh pemangku kepentingan dalam menjemput investasi di Provinsi Maluku Utara. Tujuan penelitian ini adalah menganalisis strategi mengembangkan dan meningkatkan kompetensi tenaga kerja pada berbagai prioritas pilihan investasi di Provinsi Maluku Utara. Menggunakan metode analisis deskriptif dan Analysis Hierarchy Process (AHP), hasil penelitian ini menunjukkan bahwa prioritas untuk meningkatkan kompetensi tenaga kerja di Maluku Utara dalam jangka pendek dan menengah, perlu memberi perhatian dan prioritas terhadap mutu balai latihan kerja (BLK). Selain itu, prioritas investasi yang sangat urgen untuk dipersiapkan bekal kompetensi tenaga kerjanya adalah hilirisasi pertanian dan perikanan, karena sesuai dengan karakteristik dan potensi sumber daya lokal, aspek geografis serta jaminan keberlanjutan (sustainability).           Kata kunci: Ketenagakerjaan, daya saing, investasi, pertumbuhan inklusif, AHP